Transforming commissioning at Central India Oil Refineries Ltd (CIORL) - Jain, Nikunj Kumar; Kapoor, Rohit ([London] : SAGE, 2016)
The case describes the uncertain and unavoidable events that delayed the commissioning of a transformer at central India Oil Refineries Ltd. The project was not being executed as planned, resulting in the delay of almost all of the activities. The commissioning of the transformer had become the bottleneck of the refinery because all of the pre-commissioning and commissioning activities of the refinery required steam and power, which were in turn dependent on the transformer. Project management tools such as the critical path method and programme evaluation and review technique were used to analyze the time required for the completion of the commissioning of the transformer and resource reallocation for speeding up the project.
Originally Published in: Jain, N. K., & Kapoor, R. (2014). Transformer Commissioning at Central India Oil Refineries Ltd (CIORL). Asian Journal of Management Cases, 11(2), 103-118. DOI: 10.1177/0972820114538342.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Project management -- Case studies